Diversity of drought-resistant plants and the benefits of their biomass for improving fertility of a degraded soil of Brantas River Basin - E Arisoesilaningsih; S Soejono (Brawijaya University, 2015)
In support of healthy agriculture development to improve farmer’s prosperity status, soil remediation and land conservation efforts maybe relied on the use of biomass of local vegetation. Results of field exploration conducted at Brantas Watershed of East Java indicated that there were at least 154 species of undergrowth scrubs, 47 species of agriculture-plantation crops, and 59 species of road shelter trees. The native undergrowth vegetations had undergone enormous seasonal variations. Biomass of predominance vegetations, e.g. Psophocarpus tetragonolobus, Phaseolus lunatus, Flemingia, Mimosa somian, Acacia villosa, Cassia mimosoides, Mucuna could potentially be used as organic matter sources to improve availability of nitrogen and phosphorus in soils. The amount of nitrogen and phosphorus contributed of the plant biomass significantly correlated with quality of the biomass.